The nature represented in the designs of the Awajún people in Peru - Cosme Solano, Lida (2021)
The objective of the research was to describe the designs of the Awajún people and their relationship with nature. The study was carried out in 191 students from the educational institution N ° 167411-B, Kusu Kubaim, located in the Cenepa District, Condorcanqui Province, Amazonas Region, Peru. The research was descriptive of temporal and longitudinal scope; Due to its breadth, it is micro educational; by its character, it is mixed; by its nature, it is non-experimental; for its frame, it is field. A simple descriptive design and observation and interview techniques were used; The instruments were the observation record and the interview guide. In conclusion, the main characteristic of the Designs of the Awajún Culture are symbols, small lines and points that, due to their mode, quantity, shape and location, draw various elements of nature that influence the daily life of the Awajún population, and each symbol treasures a meaning, teaching, which is often related to the patterns of coexistence of the Awajún people, and three colors prevail (black, red and white).